Pre-sowing seed treatment for enhancing frost resistance of winter wheat - Strybul, Tamara; Kovalenko, Galyna; Ryabchun, Natalia; Antsyferova, Olha; Pozdniakov, Volodymyr; Shevchenko, Nadiia (Problems of Cryobiology and Cryomedicine, 2026)
The study investigated the effect of treating winter bread wheat seeds with biologically active preparations or exposing them to negative temperatures on the frost resistance level of wheat seedlings. Cattle placenta extracts obtained by cryogenic molecular fractionation and containing a complex of biologically active substances (BAS) were used as preparations. Pre-sowing cooling of seeds was carried out at temperatures of –20, –40, –80, and –196 °C. The results of two-year experiments on determining the frost resistance of winter wheat revealed a clear trend toward an increase in this index after pre-sowing treatment of seeds by priming with BAS from animal placenta. Such treatment had a positive effect on the least frost-resistant of the studied wheat samples, the Solomiia cultivar, which was the weakest in terms of the biometric indices of the original seed seedlings. The mechanism of action of BAS as biological catalysts that contribute to increasing plant stress resistance is discussed. The role of negative temperatures as prerequisites for stratification has been determined. The data presented in the article testify to the effectiveness of the studied methods of pre-sowing treatment of winter wheat seeds regarding its frost resistance. Probl Cryobiol Cryomed. 2026; 36(2): 106—114